2011
DOI: 10.1002/lt.22312
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus quasispecies in hepatic and extrahepatic viral reservoirs in liver transplant recipients on prophylactic therapy

Abstract: The characterization of hepatitis B virus (HBV) quasispecies in different compartments in liver transplant (LT) recipients may be helpful in optimizing prophylaxis regimens. The aims of this study were to evaluate liver, peripheral blood mononuclear cells (PBMC), and plasma samples for HBV and to compare the quasispecies in hepatic and extrahepatic sites in LT recipients on long-term prophylaxis. For 12 patients followed for up to 15 years post-LT, liver, plasma, and PBMC samples [all HBV DNA-negative accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 28 publications
3
52
1
4
Order By: Relevance
“…8 Although there were only a few cases of HBV recurrence after 5 years, low-level HBV DNA was detected in 45.4% of patients who did not experience HBV recurrence during 10 y of follow-up. 11 HBV total and ccc DNA were detectable in the sera, livers, and PBMCs of almost all patients for up to 15 y post-LT. 10 Moreover, Lenci et al found that most patients with undetectable HBV DNA at transplant who received conventional HBV prophylaxis had no evidence of intrahepatic HBV total or ccc DNA; in that study, only one patient experienced HBV recurrence after transplant and tested positive for intrahepatic HBV total and ccc DNA. 9 All patients with HBV reactivation were found to have HBV total and ccc DNA in liver allografts and/or PBMCs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…8 Although there were only a few cases of HBV recurrence after 5 years, low-level HBV DNA was detected in 45.4% of patients who did not experience HBV recurrence during 10 y of follow-up. 11 HBV total and ccc DNA were detectable in the sera, livers, and PBMCs of almost all patients for up to 15 y post-LT. 10 Moreover, Lenci et al found that most patients with undetectable HBV DNA at transplant who received conventional HBV prophylaxis had no evidence of intrahepatic HBV total or ccc DNA; in that study, only one patient experienced HBV recurrence after transplant and tested positive for intrahepatic HBV total and ccc DNA. 9 All patients with HBV reactivation were found to have HBV total and ccc DNA in liver allografts and/or PBMCs.…”
Section: Discussionmentioning
confidence: 93%
“…9 All patients with HBV reactivation were found to have HBV total and ccc DNA in liver allografts and/or PBMCs. [8][9][10] Recipients with detectable HBV ccc DNA might be considered at high risk of HBV recurrence after liver transplantation. In our study, over one fifth of recipients were found to have HBV DNA in the liver or PBMCs even though they received antiviral agents and HBIG for many years after LT, and this finding was consistent with that of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okült B'li karaciğer ve/ya organ alıcılarında OBİ'li donörden organ nakli sonrası, alıcının yeni karaciğer dokusunda alıcı veya donöre ya da her ikisine ait HBV sekanslarını içeren (ek olarak HBV cccDNA) OBİ varlığı tespit edilebilmekte (64), fakat bu durumun nakil sonrası dönemde HCV pozitif hastalarda progresyon artışına neden olabildiğine dair kısmi verilerin dışında klinik önemi henüz bilinmemektedir. Ayrıca Hepatit B immünglobulin ve lamivudin tedavisi alan nakil sonrası dönemde HBsAg'si negatifleşen HBsAg pozitif organ alıcılarında da OBİ gelişebildiği rapor edilmektedir (64,65). (66)(67)(68).…”
Section: Bulaşma Riskiunclassified
“…These results are in contrast with the results of other studies in which the majority of HBsAg negative LT recipients receiving longterm HBV prophylaxis have total HBV DNA or cccDNA detectable in liver and/or peripheral blood mononuclear cells (PBMCs) supporting the rationale for an indefinite post-LT HBV prophylaxis. (12)(13)(14) We reported that 20 out of 44 (45%) HBsAg negative patients 10 years after LT receiving longterm HBIG 6 antiviral have persistence of HBV DNA in the serum (18/20), PBMC (13/20), or liver (10/20). (12) The differences between these results could be explained by differences in patient selection: HBV DNA levels at transplant, rate of HBeAg positivity at transplant, presence of HCC, duration of follow-up, type of HBV prophylaxis, frequency of antibody to hepatitis B core-related antigen (HBc) positive grafts, monocentric versus multicentric studies, sampling variability, and the sensitivity and specificity of the molecular techniques used in quantifying total and cccDNA.…”
Section: See Article On Page 1205mentioning
confidence: 99%